PERSEPSI PEDAGANG BUAH â BUAHAN IMPOR DAN LOKAL DI KOTA PADANG - Yani, Rovita - (Pendidikan Geografi, 2014)
Fruit vendors are people who conduct trading activities in the field of fruit. Usually In traditional market traders to trade on the patio fruit shops with them this or using tables. The fruit vendors usually sell a variety of fruits, of different types, shapes, names, and quality. This research aimed to obtain information, analyze, discuss, and to menggetahui perception traders imported fruits and locally in the city of Padang seen: the perception of the quality of the fruit, the fruit price, and location of the merchant. This research is qualitative. Informants in the study took the snowball sampling technique where the snowball sampling is a technique penetuan sample numbers are small at first, then enlarged (Sugiyono, 2013). Key informants Kingdom Office Market. Data were collected through observation and structured interviews and documentation. Data were collected on perceptions traders imported fruits and locally. The results of this study concluded that the perception Fruits Traders Import And Local In Padang. First, the perception of the quality of imported fruits and local fruits are very different because of imported fruit has the buyers demand quality than local fruit. Second, the perception of the price of imported fruits and local fruits are also different, more expensive imported fruit from the local fruit, but fruit imports remain attractive to buyers. Third, the perception of the location of fruit traders in Pasar Raya is still less convenient for fruit vendors, when viewed from the weather conditions were not good.